You are on page 1of 53

Standard: MM1A2e Factor expressions by greatest common factor, grouping, trial and error, and special products .

MM1A3a: Solve quadratic equations in the form ax2 + bx + c = 0 where a = 1, by using factorization and finding square roots where applicable. Todays Question: How do we factor polynomials? Standard: MM1A2e, MM1A3a.

Plot the following equations: y=x y = 2x + 5 y = -0.5x 2 SLOPE Y-INTERCEPT Hint: y = mx + b Or make a table of x and y (pick an x, calculate a y). Points plot (x, y), x is the horizontal direction (think of the horizon) y is the vertical direction

y = 2x + 5

y = -0.5x - 2
1 -8 -6 -4 -2 2

y=x

-1

-2

-3

-4

-5

Polynomial equations are really products of linear equations. Make a table of values and graph: y = (x + 2) Make a table of values and graph : y = (x 3) To distinguish between the two graphs, we can replace the ys with function notation, such as:
f(x) = (x + 2) g(x) = (x 3)

f(x) = (x + 2)

g(x) = (x 3)

-3 -2 -1 0 1 2 3 4

-1 0 1 2 3 4 5 6

-6 -5 -4 -3 -2 -1 0 1

10 8 6 4 2 -15 -13 -11 -9 -7 -5 -3 0 -1 -2 -4 -6 -8 -10

f(x) gx)
1 3 5 7 9 11 13 15

Now, multiply f(x) by g(x) to get h(x) h(x) = (x + 2)(x 3) = x2 x 6


Remember the pattern? (x + a)(x + b) = x2 + (a + b)x + ab

Add h(x) to your earlier table of values and graph h(x) on the same graph

f(x) = (x + 2)

g(x) = (x 3)

-3 -2 -1 0 1 2 3 4

-1 0 1 2 3 4 5 6

-6 -5 -4 -3 -2 -1 0 1

h(x) = f(x) * g(x) h(x) = (x + 2)(x - 3) h(x) = x2 x 6 6 0 -4 -6 -6 -4 0 6

10 8 6 4 2 -15 -13 -11 -9 -7 -5 -3 0 -1 -2 -4 -6 -8 -10 1 3 5 7 9 11 13 15

f(x) gx)
h(x)

What do you notice about the graphs of f(x), g(x), and h(x)?

f(x) and g(x) are linear h(x) is curvy the curve is called a parabola h(x) crosses the x-axis at the same places as f(x) and g(x) y = 0 at every x intercept

The domain of a function are the set of all inputs. It is the independent variable, the one you choose. The range of a function are the set of all outputs. It is the dependent variable, the one you calculate. What is the domain and range of the above functions: f(x) = (x + 2) g(x) = (x - 3) h(x) = (x + 2)(x 3) = x2 x 6

When we study Linear Equations we emphasize slope and y-intercept When we study Polynomials we emphasize zeros, x-intercepts, solutions, roots which are all different words for the basically the same thing. We start by moving all terms to one side of the equation, making them equal zero. WE ARE THEN LOOKING FOR THE VALUES OF X THAT MAKE THE EQUATION EQUAL ZERO!

Understand value of y is zero at every x intercept Understand these factors are equations and the zeros of these equations are the zeros of the polynomial. Understand that if products equal zero, that at least one of the terms must equal zero (the zero product rule) School work talks about factoring by itself, but in real life you factor to find solutions. For this reason, we will be emphasizing factoring to find solutions to problems.

The process of finding the zeros varies based on the form of the problem. If the problem is already factored and equals zero, simply use the zero product rule to find the zeros. Example: Solve (x + 3)(x 4) = 0 Either x + 3 = 0 or x 4 = 0, so x = -3 or x = 4 NOTE: The context of the problem may exclude one of the answers.

Show the Factoring by Greatest Common Factor video on my Wiki

1.

Always start by factoring out the Greatest Common Factor (GCF), and use the zero product rule to find the zeros. Example: Solve: 5x2 + 15x = 0 5*x*x+3*5*x=0 5x(5 * x * x + 3 * 5 * x) = 0 5x(x + 3) = 0 Therefore, either 5x = 0 or x + 3 = 0 5x = 0 or x + 3 = 0 5 5 -3 -3 So x = 0 or x = -3

Pg 79, # 5 30 by 5s & 36 and page 80, # 33 (8)

2.

If the problem is a trinomial of the form ax2 + bx + c = 0, we must factor the trinomial by finding the factors of a * c that add to b. If a = 1, then we are looking for the factors of c that add to b.

Show the Trinomial Factoring a = 1 video on my Wiki

Example: Solve: x2 + 9x + 20 = 0 Make a factor tree to find The factors of c that add to b: Since b is positive, we are only looking at positive numbers 4 + 5 = 9, so the factors are: (x + 4)(x + 5) = 0 x = -4 or x = -5

20 9 1 20 21 2 10 12 4 5 9 -1 -20 -21 -2 -10 -12 -4 -5 -9

Your Turn Solve: x2 - 10x - 11= 0 Make a factor tree to find The factors of c that add to b: c = -11 -11 + 1 = - 10 so the factors are (x + 1)(x - 11) = 0 x = -1 or x = 11

-11 1 -11 -1 11

-10 -10 10

Page 83, # 3 27 by 3s and 28 29 (11 problems)

Factoring a common monomial from pairs of terms, then looking for a common binomial factor is called factor by grouping. A polynomial that cannot be written as a product of polynomials with integer coefficients is called unfactorable. A factorable polynomial with integer coefficients is factored completely if it is written as a product of unfactorable polynomials with integer coefficients.

Show the Factor by Grouping video on my Wiki

Factor completely the following expressions: Example 1: 6x2 -10x -12x +20 2x(3x-5) 4(3x 5) (3x 5)(2x 4) Your turn: 6x2 + 27x + 4x2 + 18x 3x(2x + 9) + 2x(2x + 9) (2x + 9)(3x + 2x) (2x + 9)(5x)

Your turn: Factor completely the following expression: 2x3 + 14x2 + 3x + 21 2x2(x + 7) + 3(x + 7) (x + 7)(2x2 + 3)

If the equation has a common factor in each term, factor out the largest common factor and use the zero product rule to find the zeros. (2.9) Your turn: Solve 16x2 4 + 4x3 x = 0 Factor by grouping: 4(4x2 1) + x(4x2 1) = 0 The Greatest Common Factor is (4x2 1), so (4x2 1)(4 + x) = 0 x = 0.5 or x = -4
4.

Page 95, # 5 30 by 5s and 31 & 32

If the polynomial has two terms, look to see if they contain only the difference of squares (NOTE: THIS ONE IS VERY IMPORTANT !! ) a2 b2 = (a + b)(a b) Show the Factoring Difference of Squares video on my Wiki

Example: Find the zeros of x2 9 = 0 (x + 3)(x 3) = 0 x = -3 or x = 3

Your Turn: Solve: 9x2 - 49 = 0 (3x + 7)(3x - 7) = 0 x = 7/3 or x = -7/3

If the polynomial has three terms, look to see if they are a prefect square trinomial: a2 + 2ab + b2 = (a + b)2 and a2 - 2ab + b2 = (a - b)2

Example #1: Solve: 3x2 + 6x +3 = 0 Factor out the GCF first: 3(x2 + 2x +1) = 0 3(x + 1)2 = 0 x = -1 with duplicity of two
NOTE: You can do it the long way but it is faster if you see the pattern.

Factoring the prefect square trinomial: a2 + 2ab + b2 = (a + b)2 and a2 - 2ab + b2 = (a - b)2

Your turn: Solve: x2 - 6x +9 = 0 (x 3)2= 0 x = 3 with duplicity of two


NOTE: You can do it the long way but it is faster if you see the pattern.

Factoring the prefect square trinomial: a2 + 2ab + b2 = (a + b)2 and a2 - 2ab + b2 = (a - b)2

Your turn: Solve: 18x2 + 60x +50 = 0 2(9x2 + 30x +25) = 0 2(3x + 5)2= 0 x = -5/3 with duplicity of two NOTE: You can do it the long way but it is faster if you see the pattern.

Page 91, # 16 21 all and 28 & 29 (8)

We can find the points of intersection between two curves by setting them equal to each other and solving the equation. Popular examples are profit/loss curves and supply/demand curves

Steps to solve for the intersections:


1. 2.

1. 2.

3.

Set the equations equal to each other Move everything to one side of the equation, making that side equal zero. (HINT: Keep x2 positive) Factor Use Zero Product Rule to find the roots. Substitute the roots into the original equations to find the corresponding values of y

Example: find where the parabola f(x) = x2 + 2x -6 intersects with the line g(x) = 2x + 3 Set them equal to each other gives: x2 + 2x - 6 = 2x + 3 Move everything to one side: x2 - 9 = 0 Can be solved as special function or by square root show both (x + 3)(x 3) = 0 x = -3 or x = 3 Substitute to find the values of y: y = 9 or -3 Intersections: (-3, -3) and (3, 9)

Example: find where the parabola f(x) = x2 + 5x - 5 intersects with the line g(x) = -2x - 5 Set them equal to each other gives: x2 + 5x - 5 = -2x -5 x2 + 7x = 0 Solve be GCF: x(x + 7) = 0 x = 0 or x = -7 y = -5 or 9 Points of Intersection: (0, -5) and (-7, 9)

Your Turn: find where the parabola f(x) = x2 - 4 intersects with the parabola g(x) = 2x2 2x - 12 Setting them equal to each other gives: 2x2 2x - 12 = x2 - 4 x2 2x 8 = 0 Solve be finding factors of -8 that add to -2 (x + 2)(x - 4) = 0 x = -2 or x = 4 y = 0 or 12 Points of intersection are: (-2, 0) and (4, 12)

Example: find the length of the side of a square such that the area equals the perimeter. f(x) = A = s2 g(x) = P = 4s Set them equal to each other gives: s2 = 4s s2 - 4s = 0 s(s 4) = 0 s = 0 or s - 4 = 0 s = 0 or s = 4

Your turn: find the radius of a circle such that the area equals the perimeter. f(x) = A = r2 g(x) = P = 2r Set them equal to each other gives: r2 = 2r r2 - 2r = 0 r(r 2) = 0 r = 0 or r = 2

Solving Quadratic Equations by Square Root video on my Wiki Do some Guided Practice on page 120, especially some of 7 12. NOTE: LEAVE ANSWSER IN RADICAL FORM Solve: 4(2z 7)2 = 100

Practice: page 121, # 16 21 all and 24 - 26 all (9 problems)

Solve:

x2 2x - 80 = 0 (x - 10)(x + 8) = 0 x = 10 or x = -8

Solve:

2(2x- 3)2 + 4 = 12 2(2x- 3)2 = 8 (2x- 3)2 = 4 2x- 3 = 2 or 2x 3 = -2 2x = 5 or 2x = 1 x = 2.5 or x = 0.5

10 8 6

4
2 -15 -13 -11 -9 -7 -5 -3 0 -1 -2 -4 -6 -8 -10 1 3 5 7 9 11 13 15

f(x) gx)
h(x)

A cubic function is a nonlinear function that can be written in the standard form: y = ax3 + bx2 + cx + d

1. 2. 3.

Cubic polynomials are simply three linear equations multiplied together, just like quadratics are the products of two linear equations. Assume we have the following equations: f(x) = x+ 1 g(x) = 0.5x + 2 h(x) = 0.5x 1 The cubic is simply the product of these three: i(x) = f(x) * g(x) * h(x) i(x) = (-0.2x + 2)(x + 5)(0.3x -1) i(x) = 0.25x3 + 0.75x2 1.5x -2

We would get graphs that looked like:


10 8 6 4

f(x) = x + 1

g(x) = 0.5x + 2
-10 -8 -6 -4 -2

2 0 -2 -4 -6 -8 -10 0 2 4

h(x) = 0.5x -1
6 8 10

Describe the graph

Talk about the x intercept of the linear functions and the cubic Talk about values of x where the cubic is increasing. Talk about values of x where the cubic is decreasing Talk about local minimum and maximum Talk about end conditions when a > 0 and a < 0 What is the domain and range of the cubic?

They are not easy to factor. We have two patterns we can use: y = x3 + 3x2y + 3xy2 + y3 factors into y = (x + y)3 y = x3 - 3x2y + 3xy2 - y3 factors into y = (x y)3

y = x3 + 3x2y + 3xy2 + y3 = (x + y)3 y = x3 - 3x2y + 3xy2 y3 = (x y)3 Solve: -3x3 + 18x2 36x + 24 = 0 Factor out the GCF: -3(x3 - 6x2 + 12x 8) = 0 x = x, y = 2 Substitute: x3 - 3x2(2) + 3x(2)2 - 23 Clean it up: x3 - 6x2 + 12x - 8, which matches Factor via patterns: -3(x 2)3 = 0 x = 2 with duplicity of three

y = x3 + 3x2y + 3xy2 + y3 = (x + y)3 y = x3 - 3x2y + 3xy2 y3 = (x y)3 Your turn, solve: x4 + 15x3 + 75x2 + 125x = 0 Factor out the GCF: x(x3 + 15x2 + 75x + 125) = 0 x = x, y = 5 Substitute: x3 + 3x2(5) + 3x(5)2 + 53 Clean it up: x3 + 15x2 + 75x + 125, which matches Factor via patterns: x(x + 5)3 = 0 x = 0 or x = -5 with duplicity of three

Page 132, # 4 6 all, 11, 12, 16 (6)